Developing a dynamic multi-sectoral CGE model of the New Zealand economy - Nana, Ganesh (School of Management Working Papers, 1995)
Forward looking behaviour on the part of investors and consumers is incorporated into a previously static CGE model, forming the inter-temporal links in a new dynamic multi-sectoral model of the New Zealand economy. A model at the seven sector level of disaggregation is constructed and the Gempack suite of programs is used to obtain solutions, involving linearisation of.the model’s equations and matrix inversion, a la Johansen. Associated procedures to generate a multi-sectoral database consistent with the inter-temporal behaviour postulated and some sufficient conditions required to produce a balanced-growth steady-state solution are discussed. Simulations presented show a permanent effect on investment and GDP from a disturbance to relative prices, but no aggregate effect from an internal demand shock. The sensitivity of these comparative dynamic experiments are explored and they are found to be base independent and invariant to the length of the time horizon.